The Impact of Collaborative Learning Strategies and Learning Motivated Students on Learning outcomes and Ability in Madrasah Ibtidaiyah - Zai, Haswanti; Budianti, Yusnaili; Sahputra, Edi (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
There will be an examination of the impact of cooperative learning strategies on academic outcomes for students of Akidah Aklak at Madrasah Ibtidayah Negeri Gunungsitoli City, in this study. This study used a quasi-experimental approach. For both collaborative and competitive learning classes, a previously formed class was used for treatment, and the controlled characteristics of students were learning motivation. This method was chosen. Using a variety of collaborative learning strategies, this study found that both students with high and low levels of learning motivation at the State Madrasah Ibtidiyah in Gunungsitoli City could improve their academic performance. To teach Akidah Akhlak material, collaborative learning strategies should be used rather than competitive learning strategies.